Baseline fatty acids, food groups, a diet score and 50-year all-cause mortality rates. An ecological analysis of the Seven Countries Study. (17th November 2017) - Menotti, Alessandro; Kromhout, Daan; Puddu, Paolo Emilio; Alberti-Fidanza, Adalberta; Hollman, Peter; Kafatos, Anthony; Tolonen, Hanna; Adachi, Hisashi; Jacobs, David R.
Abstract: Objectives: This analysis deals with the ecologic relationships of dietary fatty acids, food groups and the Mediterranean Adequacy Index (MAI, derived from 15 food groups) with 50-year all-cause mortality rates in 16 cohorts of the Seven Countries Study. Material and methods: A dietary survey was conducted at baseline in cohorts subsamples including chemical analysis of food samples representing average consumptions. Ecologic correlations of dietary variables were computed across cohorts with 50-year all-cause mortality rates, where 97% of men had died. Results: There was a 12-year average age at death population difference between extreme cohorts. In the 1960s the average population intake of saturated (S) and trans (T) fatty acids and hard fats was high in the northern European cohorts while monounsaturated (M), polyunsaturated (P) fatty acids and vegetable oils were high in the Mediterranean areas and total fat was low in Japan. The 50-year all-cause mortality rates correlated ( r = −0.51 to −0.64) ecologically inversely with the ratios M/S, (M + P)/(S + T) and vegetable foods and the ratio hard fats/vegetable oils. Adjustment for high socio-economic status strengthened ( r = −0.62 to −0.77) these associations including MAI diet score. Conclusion: The protective fatty acids and vegetable oils are indicators of the low risk traditional Mediterranean style diets. KEY MESSAGES: We aimed at studying the ecologic relationships of dietary fatty acids, food groups and the Mediterranean Adequacy Index (MAI, derived from 15 food groups) with 50-year all-cause mortality rates in the Seven Countries Study. The 50-year all-cause mortality rates correlated ( r = −0.51 to −0.64) ecologically inversely with the ratios M/S [monounsaturated (M) + polyunsaturated (P)]/[saturated (S) + trans (T)] fatty acids and vegetable foods and the ratio hard fats/vegetable oils. After adjustment for high socio-economic status, associations with the ratios strengthened ( r = −0.62 to −0.77) including also the MAI diet score. The protective fatty acids and vegetable oils are indicators of the low risk traditional Mediterranean style diets.